Factors Influence Brand Awareness Towards Purchasing Intention on Susu Kental Manis Frisian Flag - Herliani Gemmy; Jony Oktavian Haryanto (International Journal of Business Studies, 2019)
Frisian Flag as a market leader dairy product in Indonesia has a large market share. However last year, brand value of Susu Kental Manis Frisian Flag has decreased dramatically. In addition, this study aimed to determine the factors that influenced brand awareness towards purchasing attention on Susu Kental Manis Frisian Flag. The type of this research was survey research by using questionnaire and took 200 respondents who knew and have tried Susu Kental ManisFrisian Flag. The data processing used structural equation modelling, this research result showed that positive factors which influenced brand awareness were attractiveness of advertisement and distribution intensity. While, brand awareness affects actual purchasing intention positively.